Merging Agents and Cloud Services in Industrial Applications. (18th August 2014) - Maturana, Francisco P.; Asenjo, Juan L.; Philip, Neethu S.; Chatrola, Shweta
Abstract : A novel idea to combine agent technology and cloud computing for monitoring a plant floor system is presented. Cloud infrastructure has been leveraged as the main mechanism for hosting the data and processing needs of a modern industrial information system. The cloud offers unlimited storage and data processing in a near real-time fashion. This paper presents a software-as-a-service (SaaS) architecture for augmenting industrial plant-floor reporting capabilities. This reporting capability has been architected using networked agents, worker roles, and scripts for building a scalable data pipeline and analytics system.